EVALUASI KEWAJARAN PEMBELANJAAN DAERAH DENGAN MENGGUNAKAN ANALISIS STANDAR BELANJA (STUDI PADA PEMERINTAH KOTA JAMBI) - Kamadie Sumanda Syafis (ABIS: Accounting and Business Information Systems Journal, 2014)
This study aimed to evaluate expenditure of Kota Jambi using analysis of standard expenditure/spending (ASB). This research is a case-based study with a qualitative approach . The research methodology is a document review and focus group discussion. Data used the analysis of standard spending-related regulation, public policy budget, while the budget ceiling priority, document of budget implementation changes, year of 2013-2014. Data were analyzed using simple regression.ASB models for socialization (dissemination) to the government of Jambi is total expenditure = 73.403.276 + 287.015 (the number of participants x number of days). Model ASB activities coaching/mentoring to the City of Jambi is total expenditure = 152.176.202 + 123.155 (the number of participants x number of days). There is only one activity that has nominal budget above the maximum limit that is the socialization of town planning regulations. ASB implementation in Kota Jambi can be applied. Based on the existing data and systems in Kota Jambi, both in 2013, 2014 and subsequent fiscal years.